Pathological findings in acute and chronic copper toxicity in rainbow trout (oncorhynchus mykiss, walbaum 1792) occurred by copper sulfate pentahydrate - Sema Öztürk; Hamdi Avcı (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed an experimental model of acute and chronic copper toxicity in the form of rainbow trout with copper sulfate pentahydrate and investigate the clinic, macroscopic and microscopic findings. Materials and Methods: In the present study, thirty rainbow trout were divided into four groups: Two experiment [(Acute Group (Group I), n:10 - Chronic Group (Group III), n:10)] and two control groups [(Acute Control Group (Group II), n:5 - Chronic Control Group (Group IV), n:5)]. Copper sulphate pentahidrate was given 2 mg/L for a 5 days and 0.5 mg/L for a 21 days in Group I and III, respectively. Results: Macroscopically, livers were swollen and had dark red color in Group I. Gills were oedematous. In Group III, liver had remarkable pale color. Gill were pale and skin was covered by mucous. In Group I, the most salient microscopic finding was seen in the liver. Degenerations were seen widely in hepatocytes. In the gills, epithelial necrotic changes with vascular lesions including edema, hyperemia and hemorrhage were observed. In the kidney, there were degeneration and eosinophilic hyalin droblets with variable sized in the cytoplasm of tubular epitheliums. Liver had diffusive degenerations in Group III. Hepatocyte nucleus has remarkable vesicular appearance in all findings. There was obvious thickness caused by hyperplasia in the gills. There was an increase in the number of mucous cell and hydropic degeneration on epithelial cells in the epidermis of the skin. Conclusion: As a result, it is recommended to consider the concentration of copper sulfate pentahydrate in water in rainbow trout aquaculture.